Biological systematics principles and applications - Brower, Andrew V.Z. (Andrew Van Zandt) 1962-; Schuh, Randall T. (Comstock Publishing Associates, an imprint of Cornell University Press, 2021)
"The book addresses the methods and philosophy of biological systematics (phylogenetics, taxonomy, and classification of living things). In particular, it emphasizes an empirical, cladistic approach, which espouses minimization of ad hoc hypotheses of evolution via the parsimony criterion for selecting preferred hypotheses of relationships, and recognition of groups based upon synapomorphies (inferred shared, derived character states) alone."